Morphological Study of the Lingula in Adult Human Mandibles of Brazilians Individuals and Clinical Implications. (2nd March 2015) - Alves, Nilton; Deana, Naira Figueiredo
Abstract : Objectives . The purpose of this research was to study, in macerated adult human mandibles, the height of the lingula and provide morphometric data for its location considering aspects such as shape of the lingula, gender, and race. Material and Methods . 132 macerated mandibles of Brazilian adult individuals, both sexes, Amerindian and Caucasian, were used. The distances: from mandibular notch to lingula; from anterior margin of ramus of mandible to lingula; from posterior margin of ramus of mandible to lingula; from mandibular base to lingula, and the height of lingula were obtained. To perform these measurements we used a digital caliper. The variables such as gender and race were analyzed. Results . The mean values found for the height of lingula and its location were determined according to the gender, race, and the lingula shape. Conclusion . This research provides additional data on height of the lingula and morphometric data for its location considering aspects such as shape of the lingula, gender, and race, information that had not been reported in the literature to date. We emphasize that a careful study considering gender and ethnic group makes procedures involving the region of lingula safer.